Penerapan Sanksi Hukum Adat Terhadap Perkawinan Pela Tampa Siri Negeri Rambatu - Picarima, Elsa Olivia; Latupono, Barzah (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2024)
Traditional marriage must be understood as a marriage that is based on the customary rules that apply in the local community. One of the sacred customs that still exists and is believed by the majority of Maluku people is Pela. As is the case in Rambatu Country and Kamarian Country which have a Pela Tampa Siri relationship. However, in 2020 and 2022 there were two couples who held Pela marriages between men from Rambatu Country and women from Kamarian Country and vice versa, men from Kamarian Country and women from Rambatu Country. The research method used is an empirical legal research method. As this research uses empirical legal facts taken directly from human behavior. The results of the research show that the implementation of Rambatu State's customary sanctions uses deliberation to reach consensus as implemented by custom. The application of these sanctions can be in the form of fines, as well as social sanctions in the form of ostracizing Pela married couples by indigenous peoples as a result of their own actions. Rambatu State customary law sanctions do not stipulate that Pela married couples must be expelled/leave the country. Therefore, married couples assume that the punishment is not so severe or binding that violations could occur in that country due to the application of sanctions that are not so severe.